2016
DOI: 10.1016/j.rse.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing postfire recovery of chamise chaparral using multi-temporal spectral vegetation index trajectories derived from Landsat imagery

Abstract: Land managers and ecologists working in Mediterranean-type ecosystems require information on postfire recovery of shrublands as a means of identifying long-term changes in these sensitive systems. This study evaluates the utility of postfire regrowth trajectories, derived from multitemporal Landsat satellite surface reflectance imagery, as a basis for estimating postfire recovery of chamise chaparral in southern California. Postfire recovery metrics are applied to time series trajectories of spectral vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 39 publications
5
62
0
Order By: Relevance
“…Other studies suggest that TCW is well suited to observe forest recovery due to its ability to track overall moisture content [43], however, in our study, we found it less reliable because of its low level of separation directly following a fire. Like Storey et al [21], we found that NBR2 has extended recovery timeframes, and may be worth considering for future post-fire recovery studies. In southeast Australia, many eucalypts have the ability to survive low and moderate fire through epicormic resprouting (Figure 9), whereas after high intensity stand replacement fires, forest regrowth is dependent on new seedlings ( Figure 10) [58], which naturally thin out as the forest matures.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Other studies suggest that TCW is well suited to observe forest recovery due to its ability to track overall moisture content [43], however, in our study, we found it less reliable because of its low level of separation directly following a fire. Like Storey et al [21], we found that NBR2 has extended recovery timeframes, and may be worth considering for future post-fire recovery studies. In southeast Australia, many eucalypts have the ability to survive low and moderate fire through epicormic resprouting (Figure 9), whereas after high intensity stand replacement fires, forest regrowth is dependent on new seedlings ( Figure 10) [58], which naturally thin out as the forest matures.…”
Section: Discussionsupporting
confidence: 79%
“…It is provided as a standard product by the United States Geological Survey (USGS), but is rarely used in the literature. Storey et al [21] found it useful for post-fire recovery assessment in chamise chaparral vegetation in southern California, while Stroppiana et al [22] used it as part of an ensemble to map burned areas.…”
Section: Introductionmentioning
confidence: 99%
“…, in the study that developed the harmonic modeling approach we adapted to detect microrefugia, demonstrated that dense time series of all available Landsat data enabled detection of subtle forest thinning. Other studies, more commonly using time series of annual images (including composite images; eg, Roy et al, 2010), emphasize the power of LTS to detect gradual processes including forest decline due to diffuse disturbances such as insect outbreaks or drought (Ahmed et al, 2017;Cohen et al, 2016;Deel et al, 2012;Kennedy et al, 2010), forest succession and woodland densification (Vogelmann et al, 2012), and variation in ecosystem recovery following disturbance (Kennedy et al, 2007(Kennedy et al, , 2010Lawrence and Ripple, 1999;Storey et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Landsat imagery covering the entire globe has been collected regularly for over 45 years and is now freely available for public use [8]. Recent studies have taken advantage of this data availability by developing time series data sets to monitor ecosystem recovery after wildfires [9][10][11]. The recovery trajectories derived from these data sets are an improvement over simple two-date change detection models because they capture the temporal variability that occurs after fires, including inter-and intra-annual trends [12].…”
Section: Introductionmentioning
confidence: 99%